Efeitos da radioterapia nas propriedades biomecânicas e procedimentos adesivos à dentina humana - Rodrigues, Renata Borges (2015)
The aim of this study was to evaluate, in vitro, the effects of radiotherapy in the biomechanical properties of dentine and microtensile bond strength (μTBS), performed either before or after radiotherapy. Chemical changes (ATR-FTIR) and mechanical properties (Vickers Microhardness - VHN and Elastic Modulus - E) (n=5) was evaluated comparing control and irradiated group. Radiotherapy was defined by application of 72 Gy dose fractionally with daily exposures of 1.8 Gy, 5 days a week, over 8 weeks. μTBS was made to compare three groups (n=10): C control, which received no irradiation; IrB - specimens were irradiated before restoration placement, and IrA - irradiated after restoration placement. After restorations were constructed, specimens were stored in distilled water for three months. Resin dentine sticks were prepared (1.0 mm2) and submitted to microtensile test followed by analysis of the pattern of failure. A tooth of each group was prepared incorporating the colorant Rhodamine and Fluorescein the primer and bond of adhesive system, to evaluation of the bond interface by confocal microscopy. The calculation of the percentage ratio between the areas of bands measured by FTIR showed an increased absorption for all bands of the irradiated group. Two-Way ANOVA showed an increase of dentine VHN after 72 Gy (p = 0.005) and a decrease of E (p < 0.001) compared with non-irradiated dentine. For μTBS there was difference in the bond strength values between evaluated groups, and the group was IrA which presented the lowest bond strength values. It was concluded that FTIR showed that the radiation alter the absorption bands of organic and inorganic content of the dentin, but was not able to damage triple helical conformation of collagen. The mechanical properties were changed. There was an increase in the VHN and decreased E. Radiotherapy performed before restoring affected the bond strength to dentin. There was a pattern of permeable adhesive interface for IrA group as well as higher prevalence of cohesive failures in this group.